Health professionals’ mental health: class leaders’perception - Ticiana Sirqueira Carvalho; Shirley Dósea; Déborah Pimentel; Maria Jésia Vieira (Rev Rene)
This study is about the health professionals’ mental health, aiming at identifying the perception they have of main problems that favor alterations in mental health, according to class leaders and coordinators of undergraduate courses in nursing, medicine, nutrition, dentistry, speech therapy, psychology, physical therapy and occupational therapy. A descriptive and exploratory method was used within the qualitative approach chosen. The research was accomplished through semi-structured interviews, by means of a form containing 41 open questions that were adapted to each interviewee’s function. Through content analysis, a lack of investments of the referred organs in relation to the mental health of the studied professional categories was revealed. However, these organs are aware that these professionals are stressed out, overloaded and some are even frustrated with the profession, compromising the attendance to the population.